Employing Forbidden Transitions as Qubits in a Nuclear Spin-Free Chromium Complex - Fataftah, Majed S; Zadrozny, Joseph M; Coste, Scott C; Graham, Michael J; Rogers, Dylan M; Freedman, Danna E (Journal of the American Chemical Society, 2016)
The implementation of quantum computation (QC) would revolutionize scientific fields ranging from encryption to quantum simulation. One intuitive candidate for the smallest unit of a quantum computer, a qubit, is electronic spin. A prominent proposal for QC relies on high-spin magnetic molecules, where multiple transitions between the many M S levels are employed as qubits. Yet, over a decade after the original notion, the exploitation of multiple transitions within a single manifold for QC remains unrealized in these high-spin species due to the challenge of accessing forbidden transitions. To create a proof-of-concept system, we synthesized the novel nuclear spin-free complex [Cr(C3S5)3]3– with precisely tuned zero-field splitting parameters that create two spectroscopically addressable transitions, with one being a forbidden transition. Pulsed electron paramagnetic resonance (EPR) measurements enabled the investigation of the coherent lifetimes (T 2) and quantum control (Rabi oscillations) for two transitions, one allowed and one forbidden, within the S = 3/2 spin manifold. This investigation represents a step forward in the development of high-spin species as a pathway to scalable QC systems within magnetic molecules.